Analisis Karakteristik FABA Sebagai Material Layering Timbunan Sampah - Ferra Fahriani; Roby Hambali (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2023)
Heaps of waste that are in the TPA must be covered with soil on a regular basis in accordance with the TPA management regulations. The provision of material (soil) as a material for covering Landfills requires a lot of money, so that the closing activities of Landfill waste often experience problems. In this research, a study was conducted on soil substitute material as a cover layer for waste piles in the form of FABA. Part of the soil material commonly used as layering is substituted with FABA mixed with lime, the lime serves to bind the soil and FABA. The composition of the mixture is FABA 75% + 5% lime + 20% soil, FABA 75% + 10% lime + 15% soil, and FABA 90% + 5% lime + 5% soil. The purpose of this study was to determine whether FABA could be used as a substitute material for layering in the development of Landfill layering technology. The mixed material was tested for strength characteristics in the laboratory in the form of permeability tests, soil unit weight, shear strength, sieving analysis, Atterberg Limit, and CBR and compaction. This material strength parameter is then used in layering modeling with the help of geotechnical software. The results showed that the FABA material mixture did not meet the requirements as a waste layering material with a permeability value that did not meet the requirements in the sanitary Landfill system, although had a good carrying capacity value based on the cohesion value and soil shear angle as well as the Landfill stability value.